The Effectiveness of Acceptance and Commitment Therapy and on Pain Intensity, Childhood Trauma, Perfectionism and Psychological Flexibility in Patients with Chronic Pain - Alizadeh, Parviz; Kooshki, Shirin; Tarvirdizadeh, Hajar (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: Chronic pain often leads to distress, morale weakness, and functional impairment, becoming a primary source of suffering and economic burden. This research aimed to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on pain intensity, childhood trauma, perfectionism, and psychological flexibility in patients with chronic pain. Materials and Methods: This applied, quasi-experimental pre-test, post-test, and follow-up study with a control group included 198 patients with chronic pain from Tehran’s pain clinics. Fifty patients were selected through purposive sampling based on inclusion and exclusion criteria and randomly divided into two groups: ACT (25 participants) and control (25 participants). Data were collected using the West Haven-Yale Multidimensional Pain Inventory (Kerns et al., 1985), Childhood Trauma Questionnaire (Bernstein et al., 2003), Frost Multidimensional Perfectionism Scale (Frost et al., 1990), and Acceptance and Action Questionnaire-II (Bond et al., 2011). The ACT for chronic pain was conducted in seven 60-minute group sessions over two months, based on a treatment package (McCracken, 2015). Data analysis utilized repeated measures ANOVA and SPSS software version 22. Findings: Results showed that ACT significantly affected pain intensity (F = 57.99, p < 0.001), childhood trauma (F = 144.38, p < 0.001), perfectionism (F = 68.87, p < 0.001), and psychological flexibility (F = 5.87, p < 0.001) in patients with chronic pain. Conclusion: ACT is effective in reducing pain severity, childhood trauma, perfectionism, and enhancing psychological flexibility in patients with chronic pain and can be used to alleviate psychological problems in these individuals.